2018
DOI: 10.31925/farmacia.2018.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Production of Phenolic Nicotiflorin in Astragalus Chrysochlorus Callus

Abstract: Astragalus chrysochlorus Boiss. & Kotschy (2n = 16) is one of the rare Turkish endemic species and it is listed in the Red Data Book of Turkish Plants as endangered. This species has been used traditionally for its wound healing properties and a crude ethanol extract prepared from the roots exhibits antioxidant and cytotoxic activities. In this study, a detailed phytochemical analysis was performed on A. chrysochlorus calli that resulted in the isolation of a major constituent. The purified molecule's structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The 1D and 2D NMR experiments and hydrolysis–GC-MS analysis of glycosides determined that compounds hecpatrin ( 4 ) , gaiadendrin ( 5 ), and puchikrin ( 6 ) had not previously been reported, while nicotiflorin ( 1 ), rutin ( 2 ), and artabotryside A ( 3 ) had already been reported, according to bibliographic comparisons [33,35,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The 1D and 2D NMR experiments and hydrolysis–GC-MS analysis of glycosides determined that compounds hecpatrin ( 4 ) , gaiadendrin ( 5 ), and puchikrin ( 6 ) had not previously been reported, while nicotiflorin ( 1 ), rutin ( 2 ), and artabotryside A ( 3 ) had already been reported, according to bibliographic comparisons [33,35,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we showed that a bioactive flavonol glucosides, nicotiflorin, accumulated in callus tissues of A. chrysochlorus which were the starting material of cell suspension cultures in this study (18). PAL is the first enzyme in biosynthesis of phenylpropanoids, that is also the key of secondary phenylpropanoid metabolism in plants (1).…”
Section: Discussionmentioning
confidence: 50%
“…NMR (nuclear magnetic resonance) analysis demonstrated that a natural flavonoid, a type of bioactive flavonol glucosides, nicotiflorin accumulated in callus tissues of A. chrysochlorus which were the starting material of cell suspension cultures (18). In this study, we have cloned and examined well studied enzyme phenylalanine ammonia-lyase (PAL) belonging to phenylpropanoid pathway, is necessary to upregulate flavonoid biosynthesis in most of the plant species.…”
Section: Introductionmentioning
confidence: 99%
“…According to Gwgotek, it regulated the skin inflammatory response upon UVB and UVA exposure and exhibited antioxidant activity as confirmed by tests such as 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) and FRAP. 71,72 Additionally, nicotiflorin (4), astragalin (5), and trans-tiliroside (6) have been reported to exhibit radical scavenging effects 41,61,73 and antiprotozoal activities [74][75][76] and serve as plant metabolites [77][78][79] ; cis-tiliroside (11) also reportedly induces a radical scavenging effect. 80 N-trans-feruloyltyramine (7) is known to act on cyclooxygenase (COX), an in vivo enzyme.…”
Section: Resultsmentioning
confidence: 99%